2016 Joint Rail Conference 2016
DOI: 10.1115/jrc2016-5771
|View full text |Cite
|
Sign up to set email alerts
|

Non-Contact Ultrasonic Guided Wave Inspection of Rails: Next Generation Approach

Abstract: The University of California at San Diego (UCSD), under a Federal Railroad Administration (FRA) Office of Research and Development (R&D) grant, is developing a system for high-speed and non-contact rail defect detection. A prototype using an ultrasonic air-coupled guided wave signal generation and air-coupled signal detection, paired with a real-time statistical analysis algorithm, has been realized. This system requires a specialized filtering approach based on electrical impedance matching due to the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…In order to properly assess the performance of the tests, receiver operating characteristic (ROC) curves were computed [ 25 ]. These plots compare the probability of detection (POD) to the probability of false alarm (PFA) for different threshold levels applied to the DI traces.…”
Section: Receiver Operating Characteristic Curvesmentioning
confidence: 99%
“…In order to properly assess the performance of the tests, receiver operating characteristic (ROC) curves were computed [ 25 ]. These plots compare the probability of detection (POD) to the probability of false alarm (PFA) for different threshold levels applied to the DI traces.…”
Section: Receiver Operating Characteristic Curvesmentioning
confidence: 99%
“…A separate finite element analysis was carried out to determine the exact shape of the pressure field generated by the air-coupled transmitter at its focal distance. 26 Based on the results of this analysis, the transmitter was simulated by exciting nodes on an 25 × 25 mm area of the rail top surface using the time-history of Figure 2(a), and with a spatial amplitude distribution as shown in Figure 2(b) and (c).…”
Section: Lisa Simulation Of Ultrasonic Wave Propagation In Railmentioning
confidence: 99%
“…In general, good agreements were found after comparing the SNRs suggested by these results with the actual SNRs of the waveforms acquired by each of the four pairs of air-coupled receivers during the field tests. 26…”
Section: Lisa Simulation Of Ultrasonic Wave Propagation In Railmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods include Ultrasonic (US) measurements, 6 Eddy Current (EC) testing, 7 Axle Box Acceleration (ABA) measurements, 8 Video Images (VI) 9 and guided-wave based monitoring. 10 An extensive review of the US, EC and VI method can be found in Refs. 11,12 along with the advantages and disadvantages of each method.…”
Section: Introductionmentioning
confidence: 99%